Crystallization mechanism and properties of a blast furnace slag glass - Fredericci, C.; Zanotto, E. D.; Ziemath, E. C. [UNESP] (Elsevier, 2000)
The complex crystallization process of a Brazilian blast-furnace slag glass was investigated using differential scanning calorimetry (DSC), X-ray diffraction, optical microscopy, transmission electron microscopy (TEM), selected area diffraction (SAD), energy dispersive spectroscopy (EDS) and micro-Raman spectroscopy. Three crystalline phases (merwinite, melilite and larnite) were identified after heat treatment between Tg (742°C) and the DSC crystallization peak (T = 1000°C). Merwinite was identified as a metastable phase. A small amount (0.004 wt%) of metallic platinum was found in the glass composition. Particles of Pt3Fe, detected by EDS and SAD-TEM, were the starting points of crystallization acting, therefore, as heterogeneous nucleating sites. Only melilite and larnite precipitated in a glass sample heat-treated at 1000°C for 1 h. The flexural strength of this crystallized sample was less than that of the glass, probably due the allotropic phase transformation of larnite. © 2000 Published by Elsevier Science B.V. All rights reserved.